The effect of health quotient and time management skills on self-management behavior and glycemic control among individuals with type 2 diabetes mellitus - Chen, Mengjie; Liu, Man; Pu, Ying; Wu, Juan; Zhang, Mingjiao; Tang, Hongxia; Kong, Laixi; Guo, Maoting; Zhu, Kexue; Xie, Yuxiu; Li, Zhe; Deng, Bei; et al. (Frontiers in Public Health, 2024)
Objective The aim of this study was to evaluate the present status of self-management behavior and glycemic control in individuals diagnosed with Type 2 Diabetes Mellitus (T2D), as well as to examine the impact of health quotient (HQ) and time management skills on both self-management behavior and glycemic control. Methods Between October 2022 and March 2023, a purposive sampling method had been utilized to select 215 participants with type T2D. The survey concluded a general information questionnaire, an HQ scale, a diabetes time management questionnaire and a self-management behavior questionnaire. The health quotient (HQ)encompasses the individuals' knowledge, attitude towards health, and the ability to maintain their own well-being. The diabetes time management questionnaire was reverse-scored, with higher scores indicating an enhanced competence in time management. The path among variables was analyzed using structural equation modeling(SEM).Results SEM showed that the direct effect of HQ on time management was -0.566 (p < 0.05), the direct effect of time management on the effect of self-management was -0.617 (p < 0.05), the direct effect of HQ on self-management was 0.156, and the indirect effect was 0.349 (p < 0.05); the relationship between health quotient and self-management was partially mediated by time management, with a mediating effect size of 68.8%. In addition, self-management had a direct effect on HbAlc, with a size of -0.394 (P < 0.05); The impacts of both HQ and time management on HbAlc were found to be mediated by self-management, with HQ demonstrating an indirect effect of -0.199(P < 0.05) and time management showing an indirect effect of 0.244 (P < 0.05).Health quotient and time management in patients with T2D serve as catalysts for self management behavior. They affect HbAlc level indirectly through self-management practices. The suggestion is to prioritize the cultivation of rational time organization and management skills in T2D patients, as well as enhance their health quotient level. This can facilitate a more effective improvement in patients' self-management behaviors, ultimately achieving the objective of maintaining optimal glycemic control.